Enhancing Teenage Mothers' Resilience in Lombok Through Strength Bombardment Technique Intervention - Mareta, Mira; Bafadal, Iqbal; Kirana, Dyah Luthfia (Jurusan Bimbingan dan Konseling Islam, 2025)
The lack of resilience in teenage mothers can lead to vulnerabilities in their cognitive, emotional, and behavioral functioning. Resilience is essential for managing the dual roles of wife and mother. This study aimed to assess the effectiveness of the Strength Bombardment Technique in enhancing resilience among teenage mothers. A pre-experimental, one-group pre-test post-test design was utilized. Twenty-one teenage mothers were selected through purposive sampling. Resilience levels were measured using an instrument based on Stoltz's theory, both before and after the intervention. Paired Sample T-Test analysis showed a significant increase in resilience (sig. 2-tailed = 0.000 < 0.05), confirming the effectiveness of the Strength Bombardment Technique. These findings suggest that the Strength Bombardment Technique is a promising method for empowering teenage mothers by enhancing their resilience.